Magnetic and electronic properties of the Cu-substituted Weyl semimetal candidate ZrCo2Sn. (22nd January 2018) - Kushwaha, Satya K; Wang, Zhijun; Kong, Tai; Cava, Robert J
Abstract: We report that the partial substitution of Cu for Co has a significant impact on the magnetic properties of the Heusler-phase Weyl fermion candidate ZrCo2 Sn. Polycrystalline samples of ZrCo2− x Cu x Sn ( x = 0.0–1.0) exhibited a linearly decreasing ferromagnetic transition temperature and similarly decreasing saturated magnetic moment on increasing Cu substitution x . Materials with Cu contents near x = 1 and several other quaternary materials synthesized at the same x (ZrCo T ʹSn ( T ʹ = Rh, Pd, Ni)) display what appears to be non-ferromagnetic magnetization behavior with spin glass characteristics. Electronic structure calculations suggest that the half-metallic nature of unsubstituted ZrCo2 Sn is disrupted significantly by the Cu substitutions, leading to the breakdown of the magnetization versus electron count guidelines usually followed by Heusler phases, and a more typical metallic non-spin-polarized electronic structure at high x .